Preferential Formation of Chlorite Over Talc During Si‐Metasomatism of Ultramafic Rocks in Subduction Zones. Issue 19 (7th October 2022) - Codillo, E. A.; Klein, F.; Marschall, H. R.
Abstract: Talc formation via silica‐metasomatism of ultramafic rocks is believed to play key roles in subduction zone processes. Yet, the conditions of talc formation remain poorly constrained. We used thermodynamic reaction‐path models to assess the formation of talc at the slab‐mantle interface and show that it is restricted to a limited set of pressure–temperature conditions, protolith, and fluid compositions. In contrast, our models predict that chlorite formation is ubiquitous at conditions relevant to the slab‐mantle interface of subduction zones. The scarcity of talc and abundance of chlorite is evident in the rock record of exhumed subduction zone terranes. Talc formation during Si‐metasomatism may thus play a more limited role in volatile cycling, strain localization, and in controlling the decoupling‐coupling transition of the plate interface. Conversely, the observed and predicted ubiquity of chlorite corroborates its prominent role in slab‐mantle interface processes that previous studies attributed to talc. Plain Language Summary: In subduction zones, talc can form during chemical reactions of mantle rocks with silica‐enriched fluids at the interface between descending oceanic plates and the overriding mantle. Its formation and distribution in subduction zones are believed to affect the volatile budget, rheological properties, and the down‐dip limit of the decoupling of the slab‐mantle interface. Therefore, illuminating the conditions that facilitate talc formation at high pressure‐temperature conditions is key in assessing its roles in fundamental subduction zone processes. Using thermodynamic reaction‐path models, we show that the formation of talc at the slab‐mantle interface is restricted to a limited set of environmental conditions, because its formation is highly sensitive to the compositions of the mantle rocks and reactant fluids. Contrary to common belief, talc is unlikely to form in high abundance in ultramafic rocks metasomatized by Si‐rich slab‐derived fluids. Rather, our models predict the ubiquitous formation of chlorite along with other silicate minerals during Si‐metasomatism due to the competing effects from other dissolved components that favor their formation over talc. This study calls into question the importance of talc during Si‐metasomatism in subduction zones but highlights the more predominant role of chlorite. Key Points: Limited talc formation by Si‐metasomatism of ultramafic rocks in subduction zones Chlorite formation is likely pervasive at the slab‐mantle interface Preferential formation of chlorite has wide‐ranging chemical and physical implications for subduction zone processes